Retirement self-efficacy: the effects of a pre-retirement strengths-based intervention on retirement self-efficacy and an exploration of relationships between positive affect and retirement self-efficacy - Peila-Shuster, Jacqueline J., author; Feller, Richard, advisor; Fruhauf (Bubien), Christine, advisor; Anderson, Sharon, committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2011)
A quasi-experimental waitlist comparison group design investigated if a strengths-based retirement workshop, based in positive psychology, helped to develop retirement self-efficacy. Retirement self-efficacy, as defined by this study, is one's belief, or confidence, in her/his ability to successfully negotiate the retirement transition to find purposeful and affirmative life engagement upon entering this new life chapter. The study also explored relationships between positive and negative affect and retirement self-efficacy. The convenience sample of adult volunteers (n = 66) were primarily white and highly educated, with a blend of males (n = 29) and females (n = 37). The sample was divided into a control/waitlist treatment group (n = 34 and 29, respectively) and an initial treatment group (n = 32). Results indicated that those participating in a strengths-based workshop made greater gains in retirement self-efficacy, with those in the waitlist treatment group making greater gains (p = .002, d = .65) than those in the initial treatment group (p = .068, d = .22). Overall, approximately 59% of participants made gains in retirement self-efficacy, and about 31% had decreases. It was also found that negative affect was more strongly correlated to pre-workshop retirement self-efficacy (r = -.50) than was positive affect (r = .26). Furthermore, while not reaching statistical significance, results indicated that participants with high negative affect made greater gains following the workshop (d = .36) than did those with low negative affect. Implications from these findings suggest that while strengths-based approaches hold promise in helping individuals develop greater retirement self-efficacy, it is a process that must also integrate one's readiness for change. Thus, a series of workshops or continued career counseling may benefit individuals approaching or in retirement. Additionally, it is important to consider that those with higher negative affect appear to have less retirement self-efficacy, but may make greater gains in developing it upon receiving a strengths-based intervention. Recommendations from this study point to the importance of defining and designing one's next life chapter rather than adhering to the notion that retirement is a pre-defined endpoint.
Keywords: negative affect; positive affect; positive psychology; retirement; self-efficacy; strengths